Just adding the 2 equations eliminates the terms in x (7x + -7x = 0) giving:-
0 + 9y = 9
y = 1
Plug this into the first equation:-
7x + 4(1) = -3
7x = -7
x = -1
Answer x = -1 and y = 1.
(x, y ) → (- 1, 1 )
given the 2 equations
7x + 4y = - 3 → (1)
- 7x + 5y = 12 → (2)
add (1) and (2) term by term to eliminate x
(7x - 7x ) + (4y + 5y ) = (- 3 + 12 )
9y = 9 ( divide both sides by 9 )
y = 1
substitute y = 1 into either (1) or (2) and solve for x
(1) : 7x + 4 = - 3 ( subtract 4 from both sides )
7x = - 7 ( divide both sides by 7 )
x = - 1
solution is (x, y ) → (- 1, 1 )